1996
DOI: 10.1016/s0735-1097(96)00276-8
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Recanalization by Elective Angioplasty Prevents Ventricular Dilation After Anterior Myocardial Infarction

Abstract: Delayed PTCA of an occluded LAD can frequently restore vessel patency. Success appears to be associated with better ventricular function and a lack of chronic dilation. Large randomized studies are warranted to evaluate the effect of delayed PTCA on late mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0
1

Year Published

1998
1998
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(31 citation statements)
references
References 37 publications
1
29
0
1
Order By: Relevance
“…We expected that primary PTCA would have a beneficial effect even for late-entry patients. A previous report 9 demonstrated that late mechanical opening of the IRA had beneficial effects on LV remodeling. However, no previous studies had demonstrated long-term beneficial clinical effects.…”
Section: Horie Et Al December 1 1998mentioning
confidence: 91%
See 1 more Smart Citation
“…We expected that primary PTCA would have a beneficial effect even for late-entry patients. A previous report 9 demonstrated that late mechanical opening of the IRA had beneficial effects on LV remodeling. However, no previous studies had demonstrated long-term beneficial clinical effects.…”
Section: Horie Et Al December 1 1998mentioning
confidence: 91%
“…6,7 Recently, Sabri et al 8 demonstrated a high initial success rate, a low complication rate, and a low incidence of reocclusion by late PTCA in a nonrandomized trial. In addition, Pizzeti et al 9 reported beneficial effects of "very late" (2 weeks after myocardial infarction [MI]) mechanical reperfusion of the IRA on left ventricular (LV) remodeling. Hochman,10 in an editorial comment on the Pizzeti report, evaluated the beneficial effects of late PTCA for occluded IRA after anterior MI but stated that a randomized trial was necessary.…”
mentioning
confidence: 99%
“…17 Dilation portends a poor long-term outcome. Prior evidence for an association between persistent IRA occlusion and late-phase LV remodeling, 18 characterized by increased contractile segment length and change in shape toward the spherical, 19 is more robust than the evidence for the association of IRA status and global LV systolic function. The present trial was able to assess the effect of late PCI of an occluded IRA on LV remodeling only as a secondary end point and only in a subgroup of patients selected on the basis of technical features of the LV angiogram and on patient compliance with the second catheterization.…”
Section: Džavík Et Al Total Occlusion Study Of Canada-2mentioning
confidence: 96%
“…Although peak CPK levels were highest among Malay patients, suggesting larger infarctions, the absolute variations were small and unlikely to be clinically significant, 20 and differences persisted after statistical adjustment. Information on heart failure was not available.…”
Section: Discussionmentioning
confidence: 81%